Border effects without borders: What divides Japan's internal trade? - Jens Wrona (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2015)
Over the last 20 years the trade literature repeatedly documented the trade-reducing effects of inter- and intra-national borders. Thereby, the puzzling size and persistence of observed border effects from the beginning raised doubts on the role of underlying political borders. However, when observed border effects are not caused by political trade barriers, why should their spatial dimension then inevitably coincide with the geography of present or past political borders? This paper identifies a "border effect" in the absence of a border. Thereby, the finding that trade between East- and West-Japan is 23.1% - 51.3% lower than trade within both country parts, is established in the absence of an obvious east-west division due to historical borders, cultural differences or past civil wars. From a rich set of explanatory variables post-war agglomeration processes, reflected by the contemporaneous structure of Japan's business and social networks, rather than cultural differences, shaped by long-lasting historical shocks, are identified as an explanation for the east-west bias in intra-Japanese trade.
Keywords: F14; F15; F12; 330; Border Effects; Gravity Equation; Intra-national Trade; Japan